Cracking an interstellar mystery. Issue 4 (1st August 2019) - McCabe, Michael
Abstract : Michael McCabe celebrates the centenary of the first observation of diffuse interstellar bands. Abstract: Michael McCabe celebrates the centenary of the first observation of diffuse interstellar bands with an overview of the lengthy – and incomplete – search for their origins.